DECONSTRUCTION OF BARONGAN IN JARANAN TURONGGO YAKSO ART THROUGH PURE-STUDY DANCE TYPE IN NGGRANG LADON WORKS - Dwi, Prisma (APRON Jurnal Pemikiran Seni Pertunjukan, 2026)
Turonggo Yakso Jaranan is one of the traditional performing arts that has developed in Trenggalek Regency, East Java, and serves as an important part of the local community's cultural identity. One of the essential elements within its performance structure is the Barongan, which is characterized by distinctive snake-like movements that are agile, powerful, aggressive, and dynamic. In addition to functioning as a supporting figure in the Turonggo Yakso Jaranan performance, the Barongan also embodies symbolic meanings representing strength, courage, protection, and the balance between human life and nature. These distinctive movement characteristics became the primary source of inspiration for the creation of the dance work Nggrang Ladon through a choreographic deconstruction approach. The choreography of the Barongan movements in Turonggo Yakso Jaranan was deconstructed into the dance work Nggrang Ladon by employing the study–pure dance type as the foundation of its creative process. The concept of deconstruction was implemented by dismantling the traditional movement structure of the Barongan and reinterpreting its movement elements without eliminating their aesthetic identity and essential characteristics. The choreography was further developed through the exploration of the elements of space, time, and energy, resulting in new movement forms that are more varied, creative, and capable of providing a different aesthetic experience from their traditional origins. Through the study–pure dance approach, the creative focus was directed toward the exploration of movement quality as the primary artistic object rather than emphasizing narrative structure or dramatic characters, as commonly found in traditional performances. The creative process consisted of several stages, including initial stimulation as the source of ideas, movement exploration, improvisation to discover movement variations, choreographic composition, evaluation of the overall choreographic structure, and refinement to enhance the artistic quality of the work. These stages were supported by the choreography theory of Y. Sumandiyo Hadi, the dance composition theory of Sal Murgiyanto, and Jacqueline Smith's dance construction method as the conceptual framework for developing the choreography. The findings indicate that the distinctive Barongan movements, such as slithering, crawling, striking, nggirap, caplok, and other characteristic movement qualities, were successfully transformed into new movement motifs through the development of levels, directions, tempo, dynamics, floor patterns, and energy qualities. This transformation produced a choreographic form that preserves the fundamental characteristics of the Barongan as a cultural identity while presenting a more contemporary and communicative movement language. Keywords: Choreographic Deconstruction, Barongan, Turonggo Yakso Jaranan, Study–Pure Dance, Nggrang Ladon.